"Il vecchio nel nuovo", presenze dell'antico negli affreschi trecenteschi della Chiesa Principesca dedicata a san Nicola, di Curtea de Argeş - Lechintan, Lucian (Orientalia christiana periodica, 2024)
This article examines the ca. 1364-1365 Byzantine frescoes in the Princely Church in Curtea de Argeş, Romania, in relation to classical imagery. Formal and iconographic content from the age of Classicism left its mark on portraiture, evangelical narrative art, and on the representation of the architectural decorations. The author introduces a compendious repertory of stylistic features revealing their theatrical character. These features are aimed at reinforcing the Gospel message. The wall-paintings reveal the dominant descriptive component of the human psyche and the use of classical schemes, widely considered the most effective means of expressing the intensity of emotions. A new system of referential strategies reassesses the language of gesture on a spectrum ranging from the classical to the caricatured. The aspect of pastiche within these decorations results from an overlay of the rigid aspect of the supporting structure yet in its elasticity the principle of non-overlapping and non-jointing is overcome.